DINAMIKA KONFLIK IDENTITAS PENGHAYAT SAPTA DARMA DI DESA SUKORENO, JEMBER, JAWA TIMUR - Fitriatul Hasanah; Ahmad Arif Widianto; Joan Hesti Gita Purwasih (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
The polemic of religious identity between “penghayat kepercayaan” (believers of indigenous religion) and followers of the official religions in Indonesia is still become a sensitive issue, which adds to the long list of marginalization of indigenous believers in Indonesia. Several forms of marginalization are: forcing to choose certain official religions in their National ID Card, the pros and cons of the burial places of the deceased indigenous believers, and restrictions on the construction of their worship places. This article aims to elaborate the dynamics of identity conflict between adherents of the Sapta Darma (one of indigenous belief) and the followers of official religions in Sukoreno Village, Jember, East Java. This study uses a qualitative approach using observation, in-depth interviews with 7 (seven) informants of Sapta Darma followers, and members of FKUB (Forum of Religious Harmony) for the data collection. The results of the study reveal that this identity polemic has made it difficult for adherents of Sapta Dharma to change their religious identity on their ID cards. As a consequence, they also have difficulty in accessing public burial places. Conflict resolution efforts are carried out through FKUB by providing socialization of knowledge on nationality and cultural perspective to the interfaith leaders. Polemik identitas agama antara penghayat kepercayaan dengan pemeluk agama resmi di Indonesia masih menjadi isu yang menambah daftar panjang marginalisasi penganut kepercayaan di Indonesia. Bentuk marginalisasi ini mengarah kepada pemaksaan pencantuman agama tertentu dalam KTP dan KK warga penghayat, pro dan kontra tempat pemakaman warga penghayat yang meninggal, dan pembatasan pembangunan rumah peribadatan bagi warga penghayat. Artikel ini bermaksud untuk mengelaborasi dinamika konflik identitas antara penghayat kepercayaan Sapta Darma dengan para pemeluk agama resmi, dengan mengambil lokasi tempat di Desa Sukoreno, Jember, Jawa Timur. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara mendalam terhadap 7 (tujuh) informan warga penghayat Sapta Darma, dan anggota FKUB (Forum Kerukunan Umat Beragama). Hasil penelitian mengungkapkan bahwa polemik identitas ini mengakibatkan warga pengahayat kesulitan dalam mengganti identitas agamanya di KTP dan KK sehingga mereka memiliki identitas ganda dan kesulitan dalam mengakses tempat pemakaman umum. Upaya resolusi konflik dilakukan melalui FKUB dengan memberikan sosialisasi wawasan kebangsaan dan pendekatan kultural dengan tokoh lintas agama.